The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.niox.2014.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiles of NO- and HNO-donor treated breast cancer cells: insights into tumor response and resistance pathways

Abstract: Nitric oxide (NO) synthase 2 (NOS2), a major inflammatory protein, modulates disease progression via NO in a number of pathologies, including cancer. The role of NOS2-derived NO is not only flux-dependent, which is higher in mouse vs. human cells, but also varies based on spatial and temporal distribution both within tumor cells and in the tumor microenvironment. NO donors have been utilized to mimic NO flux conditions and to investigate the effects of varied NO concentrations. As a wide range of effects media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 137 publications
1
20
0
Order By: Relevance
“…Although iNOS expression was negatively correlated with lesion grade in a cohort of invasive ductal breast carcinomas, 39 indicating a possible role of iNOS in the prevention of metastasis, iNOS expression has conversely been implicated as a marker of poor prognosis in several malignancies, including prostate, colon, and breast 40 . Stratification of a breast cancer patient cohort by estrogen receptor (ER) expression revealed that iNOS expression was predictive of poorer survival in ER − patients, 41 whereas high iNOS expression was similarly detrimental in a range of triple-negative breast cancer patient cohorts 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Although iNOS expression was negatively correlated with lesion grade in a cohort of invasive ductal breast carcinomas, 39 indicating a possible role of iNOS in the prevention of metastasis, iNOS expression has conversely been implicated as a marker of poor prognosis in several malignancies, including prostate, colon, and breast 40 . Stratification of a breast cancer patient cohort by estrogen receptor (ER) expression revealed that iNOS expression was predictive of poorer survival in ER − patients, 41 whereas high iNOS expression was similarly detrimental in a range of triple-negative breast cancer patient cohorts 42 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study (26) revealed that eNOS and weak iNOS were expressed in MCF-7 cells and served an important role in cell proliferation. In general, NO can stimulate the proliferation and migration of epithelial cells in addition to gene profile expression (27).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Norris et al have demonstrated that inhibition of GAPDH activity by HNO decreases glycolysis and induces subsequent downregulation of HIF-1a protein expression, thus leading to reduced angiogenesis and tumor growth (107). A recent study has revealed that several genes are uniquely expressed in human breast cancer cells in response to HNO donors, such as miR-21, heat shock protein 70, CSE, and interleukin-24 (25). These findings give new insight into the possible targets by HNO in breast cancer cells.…”
Section: Role Of Hno Donors or Its Derivatives In Different Cancersmentioning
confidence: 69%
“…HNO is also found to suppress PARP activity (136); this might improve the efficacy of the chemotherapies and radiation therapies. Moreover, in HNOtreated human breast cancer cells, the expression of CSE, TXNIP, and IL-24 was downregulated, while the miR-21 and HSP70 levels were upregulated, all of which may synergistically contribute to its anticancer effects (25). HIF-1a, hypoxia-inducible factor-1a; IL, interleukin; PARP, poly (ADP-ribose) polymerase; VEGF, vascular endothelial growth factor.…”
Section: Future Directions For Hno Research In the Cancer Arenamentioning
confidence: 99%